Sedation for Endoscopic Retrograde Cholangiopancreatography (ERCP) – A comparative study between propofol-fentanyl with Propofol-fentanyl-ketamine Combination (Central Medical College Journal, 2024)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) is a painful and long procedure requiring transient deep sedation and analgesia. The purpose of our study was conducted to evaluate and compare the sedation efficacy and propofol-fentanyl-ketamine could be a better regime than propofol-fentanyl for sedation in ERCP. Material and Method 100 ASA II-III patients, 18-60 yrs old schedule for planned ERCP procedure in the Dept. of Hepatobiliary Surgery & Gastroenterology of BSMMU. They were selected by inclusion and exclusion criteria and allocated to one of the two groups: group PF (n=50) and group PFK (n=50) by randomization. Group PF received propofol 1mg/kg + fentanyl 1µg/kg and group PFK received propofol 1mg/kg + fentanyl 1µg/kg + ketamine 0.25mg/kg and subsequent doses of propofol were given as a dose 0.5mg/kg accordingly. Recovery time was assessed from the discontinuation of procedure to modified aldrete recovery score ≥ 9. All result was expressed as number or mean ± SD or in frequencies (percentage) as applicable. The result were compiled and analyzed using SPSS-16, Student unpaired t test, Chi-square test. Result The average age of group PF and group PFK study population was 40.16(±9.34) and 44.56(±3.75) respectively whereas there average weight in initial group was 60.83(±5.54) and in the second group 58.39(±7.37). Male patients were more in both the groups. Group PF belongs to ASA II 35(70%) patients and ASA III 15(30%) patients whereas group PFK belongs to 30 (60%) and 20(40%) patients respectively. In the peroperative vital parameters, sedation related side effect as hypotension 10(20%) patients was observed in group PF and 3(6%) patients was observed in group PFK which was found statistically significant (p value 0.032) and apnea has been found 7(14%) patients in group PF and 2(4%) patients in PFK group. Which was found statistically significant (p value 0.018). No post-operative vital parameters were found statistically significant (p value >0.05). Total doses of propofol consumed was significantly higher in group PF (p